2022
DOI: 10.3390/microorganisms10081525
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Antimicrobial Stewardship Training on Calf Producers’ Knowledge, Treatment Behaviors and Quantified Antimicrobial Use

Abstract: The judicious use of antimicrobials on farms is necessary to mitigate the development of antimicrobial-resistant pathogens that compromise human and animal health. On livestock farms, veterinarians prescribe and dispense antimicrobials, but producers use rapid judgements of disease severity to make routine decisions on the initiation of empirical antimicrobial therapy. Therefore, the knowledge and skills required to accurately diagnose treatable bacterial infections is necessary for optimal antimicrobial stewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Herd-specific interventions showed a reduction in AMU. These interventions focussed on implementation of farmers and AHP education, increased health and welfare care (e.g., stable climate, management), biosecurity (external and/or internal), and vaccine strategy (Collineau et al, 2017;Speksnijder et al, 2017;Raasch et al, 2020;Gerber et al, 2021;Gomez et al, 2021;Phu et al, 2021;Pempek et al, 2022;Schreuder et al, 2022). The targeted study groups included cattle farmers, swine farmers, broiler farmers, and AHPs (Collineau et al, 2017;Speksnijder et al, 2017;Raasch et al, 2020;Gerber et al, 2021;Gomez et al, 2021;Phu et al, 2021;Pempek et al, 2022;Schreuder et al, 2022).…”
Section: Reductions In Amu At Herd Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…Herd-specific interventions showed a reduction in AMU. These interventions focussed on implementation of farmers and AHP education, increased health and welfare care (e.g., stable climate, management), biosecurity (external and/or internal), and vaccine strategy (Collineau et al, 2017;Speksnijder et al, 2017;Raasch et al, 2020;Gerber et al, 2021;Gomez et al, 2021;Phu et al, 2021;Pempek et al, 2022;Schreuder et al, 2022). The targeted study groups included cattle farmers, swine farmers, broiler farmers, and AHPs (Collineau et al, 2017;Speksnijder et al, 2017;Raasch et al, 2020;Gerber et al, 2021;Gomez et al, 2021;Phu et al, 2021;Pempek et al, 2022;Schreuder et al, 2022).…”
Section: Reductions In Amu At Herd Levelmentioning
confidence: 99%
“…A 50% reduction in AMU for calves was accomplished through didactic presentations, calfside training, and veterinarian feedback for farmers. There was also an increased understanding of AMS and higher correct identification of cases in need of AMU (50%, 73/146) vs. the control group (14.3%, 9/63) (p=0.002) (Rojo-Gimeno et al, 2016;Pempek et al, 2022). This intervention allowed for an integrated approach looking at both AMU but also testing farmer knowledge and not relying on self-reporting.…”
Section: Reductions In Amu At Herd Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Habing et al (2016) reported that only 27% of Midwestern dairy heifer calf producers had a veterinary written protocol that included a case definition to initiate therapy. Further, formal training to diagnose diseases may or may not be provided to producers, leading to large variation between individuals regarding their antimicrobial treatment practices (Pempek et al, 2022). Due to the interconnectedness between the dairy and veal industries, identifying and addressing these knowledge gaps among veal producers would provide evidence to design intervention strategies that modify producer treatment behaviours and improve antimicrobial stewardship.…”
Section: Introductionmentioning
confidence: 99%